2017
DOI: 10.1111/aas.12934
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia practices for endovascular therapy of acute ischaemic stroke: a Nordic survey

Abstract: Background: The optimal method of anaesthesia for endovascular therapy (EVT) in acute ischaemic stroke (AIS) has not been identified. Nordic departments of anaesthesiology may handle EVT cases for AIS differently. The aim of this survey was to describe the current practice patterns of Nordic anaesthesia departments in anaesthetic management of EVT in AIS. Methods: A survey consisting of 13 questions was sent to one qualified individual at all Nordic departments of anaesthesiology who manage anaesthesia for EVT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…A Nordic survey found that 84% of medical centers had institutional guidelines on anesthetic management, and 63% were able to provide a 24 h immediate response to an endovascular therapy request. Uncontrolled patient movements (82%) and loss of airway (35%) were still the most common reasons for converting to GA (39,40). Besides, a previous study found that most LVOs in Caucasians are located in proximal blood vessels, and in situ thrombus is much more common in Asians, which is more difficult to recanalize (41).…”
Section: Discussionmentioning
confidence: 99%
“…A Nordic survey found that 84% of medical centers had institutional guidelines on anesthetic management, and 63% were able to provide a 24 h immediate response to an endovascular therapy request. Uncontrolled patient movements (82%) and loss of airway (35%) were still the most common reasons for converting to GA (39,40). Besides, a previous study found that most LVOs in Caucasians are located in proximal blood vessels, and in situ thrombus is much more common in Asians, which is more difficult to recanalize (41).…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] However, there is considerable variability in practice with some institutions routinely using GA, others routinely using MAC, and yet others offering either anesthetic technique. 19,20 Essentially, although many patients receive MAC for EVT, urgent conversion to GA is undesirable especially when COVID-19 is suspected. The current pandemic has significant implications for anesthesiology and perioperative care generally.…”
mentioning
confidence: 99%
“…Patient condition is an essential factor for the choice of anesthetic strategy during EVT [ 4 ]. While GA constitutes the preferred anesthetic method in stroke patients with higher disability, unstable vital parameters, hypoventilation, loss of consciousness, and excessive movements, CS is often conducted in cooperative patients and is sometimes the preferred first-line strategy to avoid a delay of EVT [ 6 10 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%